Enzymatic removal of cellulose from cotton/polyester fabric blends - Vasconcelos, Andreia (2006)
The production of light-weight polyester fabrics from a polyester/cotton blended fabric, by means of the enzymatic removal of the cellulosic part of the material, was investigated. The removal of cotton from the blended fabric yielded more than 80% of insoluble microfibrillar material by the combined action of high beating effects and cellulase hydrolysis.Other major features of this enzymatic process for converting cotton fibers into microfibrillar material are bath ratio, enzyme dosage and treatment time.